Dynamics of Noise-Induced Cellular Injury and Repair in the Mouse Cochlea - Wang, Yong (Springer-Verlag, 2002)
To assess the dynamics of noise-induced tissue injury and repair, groups of CBA/CaJ mice were exposed to an octave-band noise for 2 hours at levels of 94, 100, 106, 112, or 116 dB SPL and evaluated at survival times of 0, 12, 24 hours or 1, 2, or 8 weeks. Functional change, assessed via auditory brainstem response (ABR), ranged from a reversible threshold shift (at 94 dB) to a profound permanent loss (at 116 dB). Light microscopic histopathology was assessed in serial thick plastic sections and involved quantitative evaluation of most major cell types within the cochlear duct, including hair cells (and their stereocilia), supporting cells, ganglion cells, spiral ligament fibrocytes, spiral limbus fibrocytes, and the stria vascularis. Morphometry allowed patterns of damage to be systematically assessed as functions of (1) cochlear location, (2) exposure level, and (3) postexposure survival. Insights into mechanisms of acute and chronic noise-induced cellular damage are discussed.